Experimental and Kinetic Study of CO Oxidation Over LaFe1-xCuxO3 (x=0, 0.2, 0.4, 0.6) Perovskite-Type Oxides - P. Rashidi Zonouz; M.E. Masoumi; A. Niaei; A. Tarjomannejad (Iranian Journal of Chemical Engineering)
In this paper, catalytic oxidation of CO over the LaFe1-xCuxO3 (x= 0, 0.2, 0.4, 0.6) perovskite-type oxides was investigated. The catalysts were synthesized by sol-gel method and characterized by XRD, BET, FT-IR, H2-TPR and SEM methods. The catalytic activity of catalysts was tested in catalytic oxidation of CO. XRD patterns confirmed the synthesized perovskites to be single-phase perovskite-type oxides. The synthesized perovskite catalysts show high activity in the range of reaction temperature (50 - 300 ºC). The substitution of Cu in B-site of the perovskite catalysts enhanced their catalytic activity for CO oxidation. Among different synthesized perovskite catalysts, LaFe0.6Cu0.4O3 has the highest activity: nearly complete elimination of CO was achieved at 275 ºC with this catalyst. Kinetic studies for CO oxidation were performed based on power law and Mars-van Krevelen mechanisms. According to kinetic calculations, the most probable mechanism is the MKV-D (dissociative adsorption of oxygen) which can predict the experimental data with correlation coefficient of R2 > 0.995.